Controllable asymmetric phase-locked states of the fundamental active photonic dimer - Kominis, Yannis; Kovanis, Vassilios; Bountis, Tassos (Physical Review, 2017)
Coupled semiconductor lasers are systems possessing complex dynamics that are interesting for numerous applications in photonics. In this work, we investigate the existence and the stability of asymmetric phase-locked states of the fundamental active photonic dimer consisting of two coupled lasers.We showthat stable phase-locked states of arbitrary asymmetry exist for extended regions of the parameter space of the system and that their field amplitude ratio and phase difference can be dynamically controlled by appropriate current injection. The model includes the important role of carrier density dynamics and shows that the phase-locked state asymmetry is related to operation conditions providing, respectively, gain and loss in the two lasers.
Keywords: photonic; phase-locked states; semiconductor lasers; photonic dimer; Research Subject Categories::MATHEMATICS